The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4103/0970-0218.62588
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B surface antigen, antibodies to the Hepatitis C virus, and human immunodeficiency virus in a hospital-based population in Jaipur, Rajasthan

Abstract: Background:Hepatitis B, hepatitis C, and HIV infections are a serious global and public health problem. To assess the magnitude and dynamics of disease transmission and for its prevention and control, the study of its seroprevalence is important. A private hospital catering to the needs of a large population represents an important center for serological surveys. Available data, at Rajasthan state level, on the seroprevalence of these bloodborne pathogens is also very limited.Objective:A study was undertaken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 10 publications
9
54
0
Order By: Relevance
“…22 In our study male gender (4.878) had higher odds of seropositivity. Similar observations were reported by Sood et al and Amidu et al 21,23 A higher prevalence of seropositivity was seen in shia sect (OR 1.40 )in our study which is in accordance with that observed by Irfa et al from Srinagar. 10 This could be explained on the basis of sharing razors and other instruments for self-inflicted injury practiced by shia community during Muharram processions and gatherings.…”
supporting
confidence: 83%
“…22 In our study male gender (4.878) had higher odds of seropositivity. Similar observations were reported by Sood et al and Amidu et al 21,23 A higher prevalence of seropositivity was seen in shia sect (OR 1.40 )in our study which is in accordance with that observed by Irfa et al from Srinagar. 10 This could be explained on the basis of sharing razors and other instruments for self-inflicted injury practiced by shia community during Muharram processions and gatherings.…”
supporting
confidence: 83%
“…4,5 Blood transfusion is an important life saving measure and an integral part of Amongst the viral hepatitis strains, Hepatitis C virus (HCV) is most dangerous etiological agent of transfusion-associated hepatitis as its morbidity rate is quite high with around 85% of the acutely infected patients progressing to chronic infection such as liver cirrhosis and hepatocellular carcinoma. 7,8 Blood transfusion is an effective mode of transmission of HCV infection as it allows a large quantum of infective virions into the susceptible patient. 3 It has been shown to be responsible for up to 90 percent of cases, previously known as Non A Non B (NANB) transfusion-related hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…It is a major public health problem, and it is estimated that over 300 million people are chronic HBV carriers worldwide [2]. HBV infection is relatively uncommon in some areas like Western Europe; however, the infection is endemic in African and Asian countries [3] [4].…”
Section: Introductionmentioning
confidence: 99%